Raman Enhancement and Photo-Bleaching of Organic Dyes in the Presence of Chemical Vapor Deposition-Grown Graphene - Weng, Jiaxin (Nanomaterials (Basel), 2017)
Fluorescent organic dyes photobleach under intense light. Graphene has been shown to improve the photo-stability of organic dyes. In this paper, we investigated the Raman spectroscopy and photo-bleaching kinetics of dyes in the absence/presence of chemical vapor deposition (CVD)-grown graphene. We show that graphene enhances the Raman signal of a wide range of dyes. The photo-bleaching of the dyes was reduced when the dyes were in contact with graphene. In contrast, monolayer hexagonal boron nitride (h-BN) was much less effective in reducing the photo-bleaching rate of the dyes. We attribute the suppression of photo-bleaching to the energy or electron transfer from dye to graphene. The results highlight the potential of CVD graphene as a substrate for protecting and enhancing Raman response of organic dyes.